Liquidity Risk, Speculative Trade, and the Optimal Latency of Financial Markets - Daniel Fricke; Austin Gerig (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Garbade and Silber (1979) demonstrate that an asset will be liquid if it has (1) low price volatility and (2) a large number of public investors who trade it. Although these results match nicely with common notions of liquidity, one key element is missing: liquidity also depends on (3) an asset s correlation with other securities. For example, if an illiquid asset is highly correlated with a liquid asset, then speculators will naturally step in and make it liquid . In this paper, we update Garbade and Silber s model to include an infinitely liquid market security. We show that when the market security is added, the liquidity of the non-market asset is still a decreasing function of volatility and an increasing function of investor participation, but it is now also an increasing function of its correlation with the market. Furthermore, we show that at a critical correlation value of 0.86, it is optimal for the asset to continuously clear, i.e., for orders to transact immediately when placed in the market. This low-latency result holds regardless of the other properties of the asset. The updated model can help answer several questions relevant to current financial markets: How and why do short-term speculators provide liquidity in markets? , How much benefit do these speculators add? , and Can extremely low-latency in markets be beneficial?
Keywords: G14; G10; G11; 330